OnabotulinumtoxinA and cognitive behavioral therapy in functional dystonia: A pilot randomized clinical trial - Vizcarra, Joaquin A.; Lopez-Castellanos, Jose Ricardo; Dwivedi, Alok K.; Schmerler, David A.; Ries, Scott; Espay, Alberto J. (Parkinsonism & related disorders, 2019)
Functional dystonia (FD) is a disabling movement disorder with limited therapeutic options. We aimed to examine the efficacy and safety of chemodenervation with OnabotulinumtoxinA (BoNT) versus placebo prior to cognitive behavioral therapy (CBT) in FD patients. FD patients with a Psychogenic Movement Disorders Rating Scale (PMDRS) score ≥ 10 and persistent dystonic posturing for ≥ 1 year were randomized to BoNT or placebo injections prior to 12 weekly individualized 1-h CBT sessions. Clinical assessments included PMDRS, Hamilton Depression Scale (HAM-D), Hamilton Anxiety Scale (HAM-A), Katz index of independence in activities of daily living (ADL), and Lawton instrumental ADL (iADL). The efficacy endpoints were the change in clinical assessments at 12 weeks from baseline between and within groups. Of 18 screened patients, 14 were randomized, and 10 completed the study. All patients showed reductions in PMDRS irrespective of treatment group at the end of the follow-up period. There was no difference in clinical assessments between groups at 12 weeks. Change from baseline in PMDRS score was significantly improved only in the CBT group with prior administration of placebo (mean change −9.0, 95% CI -16.5, −1.5; p = 0.02). CBT yielded robust improvement in FD patients but was unaffected by prior administration of BoNT. These pilot data do not eliminate the potential for examining future BoNT benefit in FD patients with selected topographical involvement, such as face or neck. •Functional dystonia is a disabling movement disorder with limited therapeutic options.•We compared Botulinum neurotoxin versus placebo prior to cognitive behavioral therapy.•There was no difference in clinical assessments between groups at 12 weeks.•Cognitive behavioral therapy improved functional dystonia severity in all subjects.